Earthquake in Peninsular Malaysia: what should we learn from affected countries? - Kamarudin, Syafila; Abu Samah, Asnarulkhadi; Zaremohzzabieh, Zeinab; D’Silva, Jeffrey Lawrence; Dahalan, Dzulhailmi; Mohamed, Nor Aini (International Journal of Academic Research in Business and Social Sciences, 2023)
Peninsular Malaysia is lucky enough in the sense that it isnt located on the Ring of Fire, the hotspot for earthquakes and volcanic eruptions. Nevertheless, since 2007, Malaysia has experienced about 40 cases of mild tremor (reported at 1.1 to 2.8 on the Richter scale) recorded at Bentong, Manjung, Jerantut, and Negeri Sembilan, respectively. Such events prove that there is an earthquake risk in Peninsular Malaysia, and this scenario leads to a crucial question, if a more significant tremor (caused by an earthquake) happens in Peninsular Malaysia, the local communities are ready and prepared for it? The main attempt of this study is to discover the preparedness of communities across the globe against earthquakes, and since the experience with disaster damage increases preparedness, several recommendations based on these global experiences have been suggested to strengthen local preparation against earthquake catastrophes. Based on the review, it can be concluded that structure, survival, behavioral factors, positive community-institution relationships, and individual differences (e.g., experience, marital status, educational background, etc.) play influential roles in strengthening the communitys preparation against the earthquake catastrophe.